BLOCKCHAIN TECHNOLOGY IN IOT: ENHANCING SECURITY AND TRUST - Gokul Balaguruswamy Naidu, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This comprehensive article explores the convergence of blockchain technology and Internet of Things (IoT) systems, focusing on their integrated approach to enhancing security and trust in interconnected digital ecosystems. The article examines the current IoT security landscape, identifying critical vulnerabilities in traditional implementations while presenting blockchain-based solutions that address these challenges. Through an article analysis of core blockchain components and their application in IoT environments, the article demonstrates how this integration strengthens device authentication, data integrity, and system security. The article extends to real-world applications across various sectors, including supply chain management, healthcare, and smart city implementations, where blockchain-IoT integration has demonstrated significant improvements in operational efficiency and security. The article also evaluates implementation strategies, examining technical considerations and practical hurdles in deployment. By analyzing current developments and future challenges, this article provides valuable insights into the transformative potential of blockchain technology in securing IoT ecosystems while addressing the complexities of scalability, energy efficiency, and standardization inreal-world implementations.